Economics of the public sector - Stiglitz, Joseph E. (W. W. Norton, 1999)
This book is divided into seven parts: Introduction; Fundamentals of welfare economics; Public expenditure theory; Expenditure programs; Taxation: theory; Taxation in the United States; Further issues.